Chronic Atrial Fibrillation - Joel Lardizabal; Sanjiv Sharma (Journal of Hypertension and Cardiology, 2013)
A concise review of chronic atrial fibrillation covers mechanisms, stroke risk, and rate versus rhythm control. It highlights anticoagulation strategies and shared decision‑making to individualize therapy.
Keywords: atrial fibrillation